Effects of eight-week high-intensity interval training on some metabolic, hormonal and cardiovascular indices in women with PCOS: a randomized controlled trail - Somayeh Mohammadi; Amirabbas Monazzami; Solmaz alavimilani (BMC Sports Science, Medicine and Rehabilitation, 2023)
Abstract Background Studies have revealed that high-intensity interval training (HIIT) has beneficial effect on hormonal, cardiovascular indices in women with polycystic ovary syndrome (PCOS). There, however, is still no comprehensive data on the type, intensity and duration of training for these women. Objective The current study aimed to investigate the effects of high-intensity interval training (HIIT) on metabolic, hormonal and cardiovascular indices in women with PCOS compared to a control group. Methods In a randomized controlled study, 28 patients (age: 23.8 ± 5.3 years, weight: 82.4 ± 9.7 kg, BMI: 30.33 ± 3.99 kg/m2) were divided into two groups including HIIT (n = 14) and the control (n = 14). The training protocol was performed with 100–110 maximum aerobic velocity (MAV), 4–6 sets, 4 laps, 3 sessions per week for eight weeks. Anthropometric indices, aerobic performance, insulin resistance and sensitivity, lipid profiles, testosterone, cortisol and hs-CRP were evaluated. Results The HIIT intervention decreased BMI, waist to hip ratio (WHR), visceral fat, insulin, insulin resistance, low density lipoprotein (LDL), atherogenic index, cholesterol and cortisol (P < 0.05). All variables remained unchanged in the control group (P > 0.05). Except for VAI, FBG, HDL, TG and AIP, the rest of the variables in the training and control groups show a significant difference (P < 0.05). Conclusion The results of the present study indicate that eight weeks of HIIT has beneficial effects on anthropometric, insulin sensitivity, fat profile, and inflammatory and cardiovascular indices in PCOS patients. It seems that the intensity of HIIT (100–110 MAV) is a determining factor in creating optimal adaptations in PCOS patients. Trail registration: IRCT20130812014333N143. Registration date: 22/03/2020. URL: https://en.irct.ir/trial/46295 .